Main Factors of Nullity of Marriage in the Chatolic Church of Bogor Diocese - Driyanto, Yohanes; Soelasih, Yasintha (Universitas Negeri Semarang, 2021)
The essence of marriage is two persons (man and woman) becoming one flesh. It comes from the will of God, so it is holy and sacred. Every couple has to maintain its unity and indissolubility until death separates them. In Catholic teaching, there is no divorce. Nevertheless, there is nullity or annulment for certain marriages. There are three kinds of marriage that can be declared null. The first, marriage that is entered into by man or woman having diriment impediment (can. 1083 -1094). The second, marriage that its matrimonial consent is not free, true, or full (can. 1095 - 1107). The third, marriage that is lack of form (can. 1108 - 1123). The Tribunal or Ecclesiastical Court carries out the process of nullity. This research, therefore, takes its emphasis on the main factors causing the nullity of marriage in the Catholic Church. The research was conducted in the Diocese of Bogor. The sampling method was purposive sampling. The number of informants was 18. In-depth interviews carried out data collection. Validity and reliability tests were conducted on informants. The analysis data was descriptive. The analysis results show that the main factor rendering null the marriage is the infidelity of the couple, communication that doesn’t work well between couples, and domestic violence.